Genebank Peer Reviews: A powerful tool to improve genebank quality and promote collaboration - Theo van Hintum; Sharon Balding; Gergana Desheva; John Dickie; María José Díez; Luis Guasch; Pavol Hauptvogel; Vojtěch Holubec; Dagmar Janovská; Ulrike Lohwasser; Isaura Martín; Ludmila Papoušková; et al. (Genetic Resources)
The conservation of plant genetic resources (PGR) is critical to ensuring global food security and agricultural sustainability. Genebanks play a vital role in ex situ conservation, complementing in situ strategies by preserving crop diversity (incl. their wild relatives) and providing access to biological materials for research, breeding and farming. However, maintaining high conservation standards and ensuring accessibility remains a global challenge. To address this, the ‘Genebank Peer Review’ system was developed as a collaborative quality assessment and improvement mechanism. This system facilitates reciprocal evaluations among genebanks, promoting transparency, capacity building and continuous improvement in conservation practices. Implemented in Europe since 2019, the peer review process involves structured self-assessments, site visits and expert evaluations, culminating in publicly available reports that guide genebanks in enhancing their operations. Feedback from participating institutions highlights the system's effectiveness in fostering knowledge exchange, strengthening professional networks and improving genebank management practices. Despite its success, challenges remain, particularly regarding expert availability and resource constraints. Future efforts should focus on institutionalizing mentorship programmes to sustain and expand the impact of Genebank Peer Reviews and monitor improvements.